Fishermen's perceptions of climate change impacts on livelihoods: a weighted average index (WAI) analysis in Bangkalan, Madura Island - Rohimah, Ainur; Setiani, Setiani; Priyanto, Moh. Wahyudi; Wijayanti, Dian Eswin (Agriekonomika, 2025)
Climate change presents a global challenge with significant implications for livelihood sustainability, particularly in coastal communities. This study explores fishermen's perceptions of climate change and its impacts on their livelihoods in Bangkalan Regency, Madura Island, Indonesia, a region where communities are directly affected through altered weather patterns, rising sea temperatures, and disrupted fishery ecosystems. Employing a quantitative approach, data were collected from 94 fishermen in Banyusangkah Village, Tanjungbumi Sub-district, selected via simple random sampling. The Weighted Average Index (WAI) method was used to analyze perceptions. The results indicate a high level of awareness among fishermen regarding certain climate phenomena, such as increased sea temperatures and the frequency of heavy rainfall, which they perceive as directly affecting fish catches and fishing safety. However, awareness of slower-onset, long-term impacts, such as tidal flooding and coastal erosion, remains low. These findings underscore the critical need for targeted educational outreach and policy interventions designed to foster community-based adaptation strategies, thereby enhancing the resilience of fishing communities in the face of increasingly uncertain environmental changes.